Effects of Dietary Phytol Supplementation on Growth Performance, Immunological Parameters, Intestinal Bacteria, and Prevention of Oxidative Stress Following Transportation of Nile Tilapia, Oreochromis niloticus - Saman Ahani; Sara Ahani; Morteza Yousefi; Ali Taheri Mirghaed; Afaf N. Abdel Rahman (Aquaculture Nutrition)
Nile tilapia, Oreochromis niloticus, (2.00 ± 0.02 g) were reared in 16 70-L tanks (40 individual/tank) and fed diets (approx. 345 g/kg protein, approx. 87 g/kg crude fat) containing 0 (CTL), 75 (PH-75), 150 (PH-150), and 300 (PH-300) mg/kg phytol (n = 4). After 60 days of feeding (4% daily), growth performance, humoral immune parameters, and gut bacteria were analyzed. Also, hepatic antioxidant parameters were determined before and after the fish were transported in plastic bags for 6 hr. The results showed that PH-75 exhibited the highest final weight (P<0.001), weight gain (P<0.001), feed intake (P<0.001), feed efficiency (P=0.015), plasma lysozyme activity (P=0.004), and intestinal Lactobacillus sp. population (P=0.017), among the treatments. The highest plasma alternative complement activity (P=0.006) and the lowest intestinal total viable bacteria (P=0.027) were observed in PH-75 and PH-150. The highest plasma alkaline phosphatase activities were observed in PH-75 and PH-300 (P=0.014). The highest blood leukocyte (P=0.008), monocyte (P=0.010), and eosinophil (P<0.001) were observed in PH-300, while the highest blood neutrophil was observed in all phytol treatments (P<0.001). The highest hepatic lipid peroxidation was observed in PH-300, whereas PH-75 and PH-150 showed the lowest values (P<0.001). The highest hepatic reduced glutathione was observed in PH-75, also PH-150 exhibited significant elevation in this parameter, compared to CTL (P<0.001). Transportation led to significant elevations in the hepatic antioxidant enzymes’ activities in CTL, PH-75, and PH-150; the highest activities were related to PH-75 and PH-150 treatments, which had also the highest post-transportation survivals (P<0.001). In conclusion, phytol is a suitable feed supplement for Nile tilapia, improving growth performance and welfare, particularly at 75 mg/kg.